Aesthetic Septorhinoplasty - Çakır, Barış (Springer International Publishing : Imprint: Springer, 2016)
This superbly illustrated book describes how techniques previously developed by Dr. Rollin Daniel for use in open rhinoplasty can be adapted for use in the closed approach. It is the author's opinion that this combination offers greater feedback during surgery, a shorter recovery period, and absence of scar. Full explanation is provided of preoperative preparation, including evaluation of the nasal surface aesthetics using the concept of geometric polygons as aesthetic subunits to define both the existing deformity and the aesthetic goals. The surgical techniques developed and modified to achieve the desired surface appearance are then described step by step with the aid of a wealth of color photos. It is illustrated how the novel dissection and redrape control methods reduce the healing time and enhance outcome, and an extensive series of case analyses is presented to document the benefits of the approach. The book is written in a "cookbook format" that will enable plastic surgeons quickly to learn how to utilize the closed approach to rhinoplasty to optimal aesthetic benefit.